Pragmatics and linguistic communication: the study of language use in real communicative situations, including linguistic politeness, convergence, and mutual understanding - Tamozhska, Iryna; Podolianchuk, Olha; Ilchenko, Iryna; Luhova, Daria; Snikhovska, Irena (Hradec Kralove : MAGNANIMITAS Assn., 2023)
This research paper focuses on the study of pragmatics and linguistic communication in real communicative situations, with a particular emphasis on law faculties. The paper explores how language is used in legal contexts, including the role of pragmatics in legal communication, the use of language in legal discourse, and the importance of effective communication skills for law students. The paper also examines the challenges and strategies for enhancing pragmatic competence in legal settings. Therefore, the aim of the paper is to study the peculiarities of communicative competence, linguistic politeness, and mutual understanding of law undergraduate students during their study at higher education institutions in Ukraine. Instruments of data collection used were analysis of scientific sources, questionnaires, interviews, and focused group discussion. Searching the problem provide the opportunities to determine the most using typical mistakes that law students make during professional communication, and describe the ways of overcoming them. The results of research made it possible to rate key components of communication skills of law students at higher education establishments that aimed at increasing the level of pragmatic competence of Ukrainian higher education law students.
Accession Number WOS:001053212700017
Keywords: HUMANITIES and RELIGION; SOCIAL SCIENCES; linguistic competence; speaking competence; communicative competence; effective communication; undergraduate students of legal major; typical mistakes; the ways to overcome